2004
DOI: 10.1002/ijc.20060
|View full text |Cite
|
Sign up to set email alerts
|

Expression mapping at 12p12‐13 in advanced prostate carcinoma

Abstract: We have previously mapped a putative prostate cancer tumor-suppressor gene to a 1-2 Mb region of 12p12-13. Initial work to identify the tumor suppressor at this locus focused on candidates previously implicated in malignancy; however, mutational and methylation analyses failed to identify significant genomic events. An alternative approach is to use expression analysis to prioritize the genes within the region of interest. This experimental design is based on the hypothesis that tumor-suppressor genes demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recently it was reported that among 22 leukemia patients analyzed, 17 were hemizygous for MKP-7/DUSP16, but no inactivating mutations could be detected (35), and investigators hypothesized that MKP-7/DUSP16 could be haploinsufficient for tumor suppression. Another group also reported that expression of MKP-7/DUSP16 gene is significantly down-regulated in both clinical tumors and cultured prostate cancer cell lines (36). These data suggest that down-regulation of the MKP-7/DUSP16 gene may be critical for initiation or progression of several tumors.…”
Section: Discussionmentioning
confidence: 86%
“…Recently it was reported that among 22 leukemia patients analyzed, 17 were hemizygous for MKP-7/DUSP16, but no inactivating mutations could be detected (35), and investigators hypothesized that MKP-7/DUSP16 could be haploinsufficient for tumor suppression. Another group also reported that expression of MKP-7/DUSP16 gene is significantly down-regulated in both clinical tumors and cultured prostate cancer cell lines (36). These data suggest that down-regulation of the MKP-7/DUSP16 gene may be critical for initiation or progression of several tumors.…”
Section: Discussionmentioning
confidence: 86%
“…BCL-G is a proapoptotic protein (Guo et al, 2001), which has been implicated in the activation of T-cells (Nakamura and Tanigawa, 2003) and has been shown to be significantly downregulated in prostate cancer compared with normal prostate tissue (Kibel et al, 2004). FAU and BCL-G have been investigated in apoptosis activation in breast cancer where studies indicate that they act through a common pathway (Pickard et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a small region of the long arm of this chromosome was sufficient to inhibit prostate cancer metastatic colonization of the Dunning AT6.1 rat prostate cancer cell line (3). Moreover, loss of heterozygosity (4) as well as reduced expression of specific genes present in a 2-Mb region of chromosome 12p12-13 has been associated with advanced prostate adenocarcinoma (5). Using irradiation, we further fragmented chromosome 12, and radiation hybrids exhibiting either tumorigenic or nontumorigenic phenotypes, depending on the portion of chromosome 12 retained, were generated.…”
mentioning
confidence: 99%